Хирургическое лечение при первичном очаге меланомы кожи - Коровин, С.И. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2010)
Проведены историческая ретроспектива и анализ многолетнего опыта практической онкологии в вопросе хирургического лечения первичного очага меланомы кожи и проблемы локальных рецидивов. Ключевые слова: меланома кожи, локальный рецидив, хирургическое лечение. The historical retrospective show and the analysis of many years experience of practical oncology in a question of surgical treatment primary skin melanoma and problems of local relapses were spent. Key Words: skin melanoma, local recurrence, surgical treatment.